2013
DOI: 10.1108/09590551311330843
|View full text |Cite
|
Sign up to set email alerts
|

Identifying seasonal variations in store‐level visitor grocery demand

Abstract: Purpose -The purpose of this paper is to understand the contribution of visitor demand to the seasonal sales variations experienced at grocery retailers in Cornwall, South West England. Design/methodology/approach -Working collaboratively with a major UK retailer provides access to store trading information and customer data from a popular loyalty card scheme. The authors use spatial analysis to identify revenue originating from outside the store catchment, and explore the spatial and temporal nature of the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…It changes by season (i.e., larger in August compared to January) therefore visitor and residential visits to these sites does increase seasonally. The seasonal change in visitor to resident retail footfall is informed by previous work by Newing et al [22,35] analysing loyalty card data for stores within this region. The calculation of overnight visitors as a separate type of origin centroid dataset is described in the next section.…”
Section: Spatiotemporal Population Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…It changes by season (i.e., larger in August compared to January) therefore visitor and residential visits to these sites does increase seasonally. The seasonal change in visitor to resident retail footfall is informed by previous work by Newing et al [22,35] analysing loyalty card data for stores within this region. The calculation of overnight visitors as a separate type of origin centroid dataset is described in the next section.…”
Section: Spatiotemporal Population Modellingmentioning
confidence: 99%
“…We make use of a novel dataset estimating the seasonal and spatial distribution of overnight visitors (Table 2). These estimates account for all visitors staying overnight within the study area (domestic and international tourists) and were built from the "bottom-up", taking individual accommodation "units" as the building block, aggregated to the unit postcode or census Output Area (OA) level to form visitor "origins", as outlined fully in Newing et al [35]. Accommodation units may represent commercial accommodation (e.g., a hotel room, self-catering cottage or camping pitch), or be drawn from the existing housing stock (holiday/second home, or home of a hosting friend or relative).…”
Section: Seasonal Population Fluctuationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, Newing et al (2012;2014) demonstrated that visitor expenditure makes up a considerable proportion of sales within some grocery stores, yet grocery retailers have very limited knowledge of the drivers behind this form of expenditure. Location planning teams working within major grocery retailers have a long-established and important role in estimating revenue for proposed new stores and in managing the existing store portfolio by monitoring store performance against predicted revenue (Bennison et al, 1995; see also Wood and Reynolds (2011) for a detailed discussion of the role, scope and influence of location planning within a range of UK retailers ).…”
Section: Introductionmentioning
confidence: 99%
“…Cornwall is used as a study area as Newing et al (2012) demonstrated that at grocery stores in certain Cornish tourist resorts, visitor expenditure was found to represent over 50% of weekly store revenue during the peak tourist season, and it is inferred that this expenditure is driven by self-catering accommodation. Self-catering accommodation is known to generate visitor expenditure on food and drink as, by definition, meals are not provided as part of the accommodation.…”
Section: Introductionmentioning
confidence: 99%